The impact of the price of gold on the profitability of the Indonesian Sharia Bank and its impact on the economic well-being of the people - Suhairi Ritonga; Marliyah Marliyah; Aqwa Naser Daulay (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
This study aims to examine the impact of gold prices on the profitability of Bank Syariah Indonesia (BSI), with a focus on its implications for social and economic issues within society. The research subjects include monthly gold price data from 2019 to 2023 and BSI’s financial reports for the same period. The study employs a quantitative approach using simple linear regression analysis with SPSS Version 23. The results reveal that gold prices significantly affect BSI's profitability, as measured by Return on Assets (ROA). The T-test indicates that from 2021 to 2023, fluctuations in gold prices have a significant impact on BSI’s profitability, with a T-value of 13.526 > T-table 1.67 and a significance value of 0.000 < 0.005. The coefficient of determination shows that gold prices account for 75.9% of the variation in BSI’s profitability. These findings highlight how gold price can influence Islamic banking products and impact investment decisions within the community. The results suggest the need for better risk management strategies by BSI to mitigate the effects of gold price volatility and address potential social and economic instability arising from asset price changes. This study provides valuable insights into how gold price can affect economic well-being and the stability of the Islamic banking sector.